Argumentación jurídica de la imputabilidad de los adolescentes a partir de los 16 años cuando comenten delitos graves. - Villarreal Montenegro, Andrea Lisbeth (2015)
In Ecuador some of the causes of this social problem is the loss of moral values, the influence of violent programs and broadcast news media, family abandonment and especially poverty. Over the years it was considering creating laws and all institutions who are responsible for ensuring the welfare and rights among which are the Council for Children and Adolescents and DINAPEN. Ecuadors constitutional reform lists the rights and obligations and all the principles to be followed in the process of judging that group. Ecuador has created a penal policy that is just the set of decisions and practices from the State organize, maintain, control and define non- harmonious social relations among members of a society through the criminal justice system, but in this research has found that the state still does not provide enough support and especially enough interest in improving rehabilitation and educational measures. It should be taken into account that the rights of adolescents are many but the most important is to have a decent life when they commit any offense or crimebe welcomed by a specialized justice policy violence prevention and good management of Institutional Intermment Centers and providing alternatives that lead him to adolescent social adjustment, To conclude the research has done a brief historical analysis of the doctrine and laws on the Protection of Adolescent Offenders Spain and some countries, which coincide with further reforms of rehabilitation considering international recommendations.